Biodiversity of epifauna in the ports of Southern Baltic Sea revealed by study of recruitment and succession on artificial panels. (5th February 2021) - Witalis, B.; Iglikowska, A.; Ronowicz, M.; Kukliński, P.
Abstract: Ports are highly dynamic environments that are under substantial anthropogenic pressure generated by activities related to the fishery, transhipment of cargo and passenger traffic. Thus, seaports are exposed to physical disturbances, chemical pollution and biological invasions. Yet knowledge about biotic part and the influence of anthropogenic pressure on it in seaports often does not exist. The main aim of this study was to assess the biodiversity of the hard-bottom epifauna by examination of the course of the recruitment and succession processes in the poorly known port basin ecosystem of the southern Baltic Sea at the ports of Gdańsk, Gdynia and Władysławowo. We wanted to test whether the different port areas had their unique species diversity and compositions. In all investigated ports we found relatively low biodiversity but high recruitment activity of sessile fauna. Six epifaunal species were observed, and Amphibalanus improvisus was consistently the dominant species (up to 47, 126.5 ± 2747.1 SD individuals per 225 cm 2 in July in Gdynia port). Seasonality was found to be the main factor shaping recruitment and further development of the sessile assemblages, and the seasonal sequences of epifaunal occurrence were similar in the three examined ports. Furthermore, the epifauna of all ports showed homogenous species richness, composition and abiotic characteristics, although in the Władysławowo port, which is more exposed to the open sea, a higher abundance of meroplankton and greater shares of accessory species ( Mytilus spp., Limecola balt h ica, Cerastoderma glaucum and Mya arenaria ) were found. The assemblage structures of the ports resembled those of nearby natural system (Gulf of Gdańsk); thus, the port ecosystem seems to be an integral part of the surrounding natural habitat. Two years of monthly observations did not reveal any new non-native species in the examined study area. Highlights: Seaports are highly disturbed and polluted area for benthic sessile fauna. Seasonality was found to be the main factor shaping recruitment of epifauna. Epifauna of all studied ports showed homogenous species composition. Epifauna assemblage structures of ports resembled those in ambient natural habitat. No new non-native species was found in the examined study area